The Difficulties which Face Public Basic School Principals in Jarash Governorate in Editing Formal Letters and Correspondence and Means of Dealing With These Problems as Perceived by Them - جمعة سريح الكبيسي عبد الله عيسى عمايره (College of Education for Women, 2019)
This study aimed at identity baying the difficulties which face public basic school principals in jar ash governorate in editing formal letters and correspondence and means of debating with these problems to collect data the researchers developed a question air were established the population of the study which represents its sample consisted of 129 principals 65 males and 64 females The results of the study revealed that the principals face difficulties in office and file management in preparing plans and reports and writing formal letters and answering them saved recommendations were presented among which were organizing training sessions and workshops to train the principals on how to dead with there problems. Keywords: difficulties formal correspondence letter editing